SIMULASI PENGELUARAN PEMERINTAH DAN DAMPAKNYA TERHADAP KINERJA EKONOMI MAKRO: SUATU MODEL COMPUTABLE GENERAL EQUILIBRIUM - Indra Maipita (Universitas Negeri Medan, 2012)
This study analyzes the impact of increased government spending on macroeconomic performance, using AGEFIS; a Computable General Equilibrium Model. Simulations carried out with the three scenarios in the sector Construction, Electricity, and Land Transportation. The simulation results shows that, in general, an increase in government spending have a positive impact on macroeconomic performance and increase household income. increase in government spending in the Construction sector provides better impact on increasing household income compared with other sectors, while in the electricity sector have no effect